The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.trac.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Developments and interlaboratory study of the analysis of short-chain chlorinated paraffins

Abstract: To survey the conformity and quality of the results between laboratories for short-chain chlorinated paraffins (SCCPs) determination, we reviewed current and novel analytical methods and organized four worldwide laboratory exercises between 2011 and 2017. Participants were requested to analyse test solutions and extracts of various matrices with their method of choice. Thirty-three laboratories participated (9e22 per round), of which 55e81% were able to submit data. Large differences in results between laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 33 publications
3
43
0
Order By: Relevance
“…This is comparable with the average CP levels ( n = 3) observed in our study, 7.1 ± 0.2 μg/g ( R 2 = 0.93) for the SCCPs, 10 ± 0.2 μg/g ( R 2 = 0.71) for the MCCPs. Especially considering that the between lab coefficient of variation (CV) of the laboratory exercises organized between 2011 and 2017 were 23–137% 23 and that two different analysis techniques are used, the GC–MS operated in electron capture negative ion (ECNI) chemical ionization mode by Shang et al 22 and the APCI-qTOF-MS method in our study. In addition to CPs various other chlorinated compounds have been detected in the NIST SRM2585 dust sample.…”
Section: Methodsmentioning
confidence: 99%
“…This is comparable with the average CP levels ( n = 3) observed in our study, 7.1 ± 0.2 μg/g ( R 2 = 0.93) for the SCCPs, 10 ± 0.2 μg/g ( R 2 = 0.71) for the MCCPs. Especially considering that the between lab coefficient of variation (CV) of the laboratory exercises organized between 2011 and 2017 were 23–137% 23 and that two different analysis techniques are used, the GC–MS operated in electron capture negative ion (ECNI) chemical ionization mode by Shang et al 22 and the APCI-qTOF-MS method in our study. In addition to CPs various other chlorinated compounds have been detected in the NIST SRM2585 dust sample.…”
Section: Methodsmentioning
confidence: 99%
“…This is also very reasonable if we consider the results from the available interlaboraty studies with SCCPs. [83][84][85] Tomy et al 83 found differences between the assigned values and the reported concentrations from -30% to 310%. The latest interlaboratory study of van Mourik et al 85 reported differences of up to 54%.…”
Section: General Remarksmentioning
confidence: 97%
“…[83][84][85] Tomy et al 83 found differences between the assigned values and the reported concentrations from -30% to 310%. The latest interlaboratory study of van Mourik et al 85 reported differences of up to 54%. Therefore, we will take a more general approach and interpret ranges of the measured concentrations rather than single values.…”
Section: General Remarksmentioning
confidence: 97%
“…This requires reliable analytical methods and agreement in results between laboratories. However, recent proficiency tests show large differences in reported SCCP levels for the same samples (naturally contaminated) between laboratories (up to 137% coefficient of variation) [6] . This is mainly due to their challenging determination, as described extensively elsewhere [7] .…”
Section: Introductionmentioning
confidence: 99%